The Effect Of Technological, Organizational, And Environmental Factors On Adoption Of Electronic Commerce By Small And Medium Enterprises In Kuwait: The Roles Of Attitude And Innovativeness - Al Enezi, Saleh O. M. R. (2021)
This study examined the relationship between perceived relative advantage (PRA), perceived compatibility (PCO), perceived complexity (PCX), organizational readiness (ORD), IT knowledge (ITK), competitive pressure (COP), suppliers/customers' pressure (SCP), and SMEs' E-commerce adoption. Furthermore, the study examined the mediating role of attitude on these relationships as well as the moderating role of innovativeness on the attitude - E-commerce adoption link. Data were collected from the SMEs operating in Kuwait using a cross-sectional study design.